Pengaruh Komunikasi dan Disiplin Kerja Terhadap Kerja Sama Tim Karyawan Non Medis Pada PT Horas Insani Abadi Pematangsiantar - Darwin Lie; Christine Loist; Ady Inrawan; Edy Dharma; Yulianda Ranuwisastri (Strategic: Journal of Management Sciences, 2022)
Objective. The aims of this study are: 1. To find out the description of communication, work discipline, and teamwork of non-medical employees at PT Horas Insani Abadi Pematangsiantar. 2. To determine the effect of communication and work discipline on the teamwork of non-medical employees at PT Horas Insani Abadi Pematangsiantar simultaneously and partially. Research Methods. The place of research was conducted at Horas Insani Hospital Pematangsiantar which is located on Jl. Medan Km 2.5, Siantar Martoba District, Pematangsiantar City, North Sumatra. In this study, the population used were all non-medical employees of PT Horas Insani Abadi Pematangsiantar, totaling 105 people. Results. The results of this study can be concluded as follows: Communication, work discipline, and teamwork of employees are good. There is a positive influence between communication and work discipline on employee teamwork. There is a strong and positive relationship between communication, work discipline and employee teamwork. Then whether or not the teamwork of employees can be explained by communication and work discipline. The results of the hypothesis test stated that H0 was rejected, meaning that communication and work discipline had a positive and significant effect on employee teamwork at PT Horas Insani Abadi Pematangsiantar either simultaneously or partially. Conclusion. The suggestions from the results of this study are: To make communication effective, the hospital should provide facilities in the form of shelves where patient status is stored. To improve work discipline, the hospital should provide sanctions in the form of a warning to employees who violate the rules set by the hospital so that employees are more disciplined at work. To improve teamwork, employees should have discussions related to work so that good cooperation can be established.